2010
DOI: 10.1074/jbc.a109.073429
|View full text |Cite
|
Sign up to set email alerts
|

TILRR, a novel IL-1RI co-receptor, potentiates MyD88 recruitment to control Ras-dependent amplification of NF-κB.

Abstract: Because of clerical errors in preparing the figures, in Fig. 1A, the last portions of the mouse and human TILRR sequences are not aligned with the consensus sequence, and the human form is mislabeled as 716 amino acids (aa). In Fig. 2C (and on page 7227, right column, line 4), the most potent form of the human protein is mislabeled as 710 aa. Supplemental Fig. S1 correctly shows the alignment and the length of the human TILRR protein as 715 aa, with the most potent form, lacking the N-terminal 6 aa, as 709 aa.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
24
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(25 citation statements)
references
References 0 publications
1
24
0
Order By: Relevance
“…Our earlier studies show that TILRR associates with IL-1RI to amplify IL-1-induced activation of NF-B and inflammatory genes (10). Here we demonstrate that TILRR similarly potentiates IL-1-induced anti-apoptotic responses.…”
supporting
confidence: 58%
See 2 more Smart Citations
“…Our earlier studies show that TILRR associates with IL-1RI to amplify IL-1-induced activation of NF-B and inflammatory genes (10). Here we demonstrate that TILRR similarly potentiates IL-1-induced anti-apoptotic responses.…”
supporting
confidence: 58%
“…Plasmid cDNAs and siRNA Constructs and TransfectionPlasmids containing wild type or mutant TILRR cDNAs, TILRR-specific or random siRNAs, wild type or mutant IL-1R1 cDNAs, dominant negative (DN) MyD88 or DNTRAF6, or the IL-8 promoter (IL-8-Luc, -EGFP) were transfected by calcium phosphate, as described previously (10), or by PolyFect (Qiagen) according to the manufacturer's instructions. All experiments used constant levels of DNA and included empty vector (mock) or random siRNA (no genomic equivalent) as controls, respectively.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A splice variant of FREM1, TILRR, has been shown to influence the immune response via two GAG (glycosaminoglycan) binding sites that bind to interleukin-1 receptor 1 (IL-1-R1). The binding increased MyD88 recruitment to IL-1-R1 with subsequent NF-B activation and enhanced inflammatory response (52). This isoform of FREM1 is a particularly attractive candidate for protection, as these are immunological correlates (1,2,25,30,46) to the HESN phenotype in the Pumwani cohort.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have revealed that mechanotransduction is a physiological process that allows cells to sense and respond to mechanical stress, 38 and several molecules and receptors that have intermediary roles in mechanotransduction have been identified. 3,[39][40][41][42][43][44][45][46] One of these receptors is the Toll-like receptor-2 (TLR2), 42,43 which is expressed on the villus epithelium and on the FAE and in M cells of PPs. This receptor plays a critical role in the early, innate immunoresponse and invasion of pathogens by sensing microorganisms.…”
Section: Discussionmentioning
confidence: 99%